Priority areas of strategic management of higher education institutions - Rasulkhodjayeva Madina Tursinalievna (Euro Asian Journal Publishing, 2024)
In this article, it is considered that the relevance of the problem of education quality management is related to socio-cultural changes in the society and changes in the state's education policy. To study the problematic and multifaceted educational system of the philosophical and socio-economic analysis of the quality of education, to determine the responsible subjects - the stakeholders of higher education, their level of satisfaction and, based on this definition, The strategy of university activity was studied. Ensuring the effectiveness of the reforms implemented in the higher education system of our country directly depends on qualified education managers. The essence of the large-scale reforms implemented in Uzbekistan in the following years is, first of all, consistent development of all sectors of our economy. In the successful implementation of this task, training of potential young personnel with in-depth knowledge and practical skills for industries has a special place
Keywords: educational institutions; international rating; educational system